142 Effects of Increasing Dietary Standardized Ileal Digestible Lysine Levels on Growth Performance of 11- to 25-Kg Pigs Sired by PIC 337 High Index Boars. (12th April 2022) - Lu, Ning; Vier, Carine M; Dritz, Steve; Navales, Ron A; Cast, Wayne R; Zaragoza, Luis E; Orlando, Uislei A
Abstract: Our objective was to determine the effects of increasing dietary standardized ileal digestible (SID) lysine (Lys) on growth performance of late nursery pigs. A total of 1, 116 pigs (PIC 337×Camborough, initially 11.1±0.11 kg) were used in a 21-d study. The pigs were sired by boars ranked in the top 15% of a selected PIC elite boar stud based on index. Pens of pigs were blocked by body weight and randomly allotted to 1 of 5 treatments that contained 1.13, 1.26, 1.32, 1.38, and 1.51% of dietary SID Lys (corresponding to 90, 100, 105, 110, and 120% of PIC SID Lys recommendations). Diets were corn-soybean meal-based and contained 2, 385 Kcal of NE/kg. There were 9 mixed gender pens per treatment and 24 or 25 pigs per pen. Data were analyzed using generalized linear and nonlinear mixed models with pen as the experimental unit. Competing models included linear, quadratic polynomial (QP), broken-line linear (BLL), and broken-line quadratic (BLQ). Increasing SID Lys concentration improved average daily gain (ADG, linear, P = 0.001) and gain to feed ratio (G:F, quadratic, P = 0.011, Table 1). Although the best fitting model for ADG was the linear, the greatest improvement was observed as SID Lys level increased from 1.13 to 1.32%. The best-fitting models for G:F were BLL, BLQ, and QP. The BLL and BLQ models estimated the breakpoint at 1.31% (95% CI: 1.24 to 1.37%) and 1.30% (95% CI: 1.24 to 1.37%), respectively. The QP model estimated the maximum G:F at 1.44% (95% CI: 1.35 to >1.51%), with 98.7% of maximum G:F achieved at 1.30%. Increasing dietary SID Lys levels marginally reduced removal and mortality rate (linear, P = 0.061). In conclusion, the estimated optimum SID Lys concentration for 11- to 25-kg pigs sired by high index boars ranged from 1.30 to 1.44%, depending on the response criteria and statistical model.